Measles rubella campaign - India’s journey from expanded program on immunization to measles elimination - Kaur, Amarpreet; Kaur, Gurmeet; Padda, Preeti; Sethi, Amanpreet; Rai, Seema; Gupta, Harshvardhan; Kaul, Varun (Indian Journal of Child Health, 2019)
Infectious diseases have always been a major cause of mortality and morbidity in children under 5 years of age and more so in developing countries like India. Steps toward control of these infectious diseases, especially the vaccine-preventable diseases, have been the priority of Indian Government. Smallpox was eliminated followed by polio and next target being measles. Although the journey has been tough, finally, the results are appreciable considering the large population and limited resources of the country. India has traveled a very long distance from the introduction of vaccination and acquiring country’s vaccine manufacturing to finally eliminating measles.